CONTRIBUTION TO RESEARCH OF STOJAN NOVAKOVIĆ AS A SCHOLAR OF SERBIAN NATIONAL STUDIES (Heritage, 2025)
This paper examines a passage in Stojan Novaković’s text The Uprising Against the Dahias. The work is historiographical in nature, and in this particular paragraph Novaković presents an observation of a seemingly accidental coincidence, which he does not attempt to explain. He notes a correspondence between the borders and capitals of the last medieval Serbian state and the first insurgent state of the 19th century. Between these two lies several centuries of Ottoman rule over the Serbs, which Novaković at that moment chooses to ignore in order to establish a continuity of Serbian statehood across that period.The fact that Novaković does not explain what he intended to achieve with this remark leaves room for interpretation. We have therefore adopted an interpretative approach, placing the passage in three contexts in which it may be explained.First, we placed it in the narrowest framework, formed by Novaković’s scholarly hypothesis regarding the long duration and unchanging nature of the Serbian worldview. From this standpoint, the insurgents merely recreated the Serbian state remembered through ecclesiastical and popular tradition.Second, we situated the subject in the broader context of Serbian scholarship of the time, drawing on Aleksandar Miljković’s thesis on 19th-century Serbian science as a specific part of national culture that holistically studies the Serbian people. This differs from science divided by theoretical disciplines, as its goal is not solving abstract scientific problems but understanding the people in all dimensions and forms of their existence. Scholars are loyal to the people to whom they belong and work for their benefit. Novaković’s engagement in Serbian national scholarship can explain why he perceived something a specialized, theory-oriented scientist might not notice.Finally, we also viewed the passage through the lens of an anthropological theory developed by Swiss anthropologist Christian Giordano. His theory deals with the different treatment of time in historiographical and anthropological approaches. In this passage, Novaković steps out of historiographical time and into anthropological time, where events are connected by meaning rather than chronological sequence.These three interpretive contexts are interconnected: Stojan Novaković consciously belonged to the Serbian people as part of its loyal elite; he engaged in a type of scholarship that was a product of national culture; and he held the view of national mentality as an uninterrupted continuity from the settlement of the Slavs to the establishment of modern social institutions. These few interrelated facts enabled Novaković to perceive continuity even where it does not exist in socio-political reality—because it was preserved in ecclesiastical-popular tradition as a spiritual reality, from which it could rematerialize under favorable conditions.We conclude that these connected motives most likely led Novaković to include the observation of a peculiar coincidence in his historiographical text. The first motive is scholarly—as further confirmation of his hypothesis on the longevity of Serbian worlview and cultural traditions. The second is personal—stemming from his loyalty to the people he belonged to, whose way of life and thought he understood, and toward whom he felt a sense of responsibility as a public intellectual. The third motive is political—by scientifically establishing continuity between the medieval and modern Serbian states, Novaković aimed to legitimize the latter as a continuation of the former state tradition. In doing so, he sought to silence critics who viewed the modern Serbian state as an illegitimate act of defiance by insignificant Serbs against the lawful imperial order in 19th century Europe. This issue had not lost its relevance even a century after the events, at the time Novaković was writing about them in his studies The Uprising Against the Dahais and The Resurrection of the Serbian State.
Keywords: Stojan Novaković, The Uprising Against the Dahias, The Resurrection of the Serbian State, meaningful coincidence, continuity of Serbian statehood, Serbian national studies, anthropological and historiographical time.